How can we characterise family literacy programmes in England, Ireland and Malta: a comparative case study - Rose, Anthea (2008)
Family literacy programmes have become an increasingly popular pedagogical tool utilised by policy makers to help address the literacy needs of families with low skill competencies and who are viewed as economically and socially underachieving. Taking a comparative case study approach, in this research I consider what benefits family literacy programmes have for the literacy skills of families.